In vitro culture systems as an alternative for female reproductive toxicology studies. Issue 2 (15th March 2019) - Guerreiro, Denise Damasceno; Mbemya, Gildas Tetaping; Bruno, Jamily Bezerra; Faustino, Luciana Rocha; de Figueiredo, José Ricardo; Rodrigues, Ana Paula Ribeiro
Summary: Studies have shown that daily exposure to different products, whether chemical or natural, can cause irreversible damage to women's reproductive health. Therefore it is necessary to use tests that evaluate the safety and efficacy of these products. Most reproductive toxicology tests are performed in vivo . However, in recent years, various cell culture methods, including embryonic stem cells and tissues have been developed with the aim of reducing the use of animals in toxicological tests. This is a major advance in the area of toxicology, as these systems have the potential to become a widely used tool compared with in vivo tests routinely used in reproductive biology and toxicology. The present review describes and highlights data on in vitro culture processes used to evaluate reproductive toxicity as an alternative to traditional methods using in vivo tests.